2017
DOI: 10.7150/jca.17513
|View full text |Cite
|
Sign up to set email alerts
|

Anal adenocarcinoma requires prophylactic inguinal nodal treatment: Results from a single Chinese institution

Abstract: Background: Literature pertaining to prophylactic inguinal nodal treatment for anal adenocarcinoma in China is scarce.Methods: In this retrospective study, we analyzed 126 patients from 1965 to 2015. Among these, 67 patients received surgery only, 18 patients received chemoradiotherapy only, 27 patients received a combination of both, and the remaining 14 patients received palliative treatment.Results: The median follow up period was 30 months. The 1-year, 3-year, and 5-year overall survival rates were 85.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
0
9
2
Order By: Relevance
“…The present study found that, for long-term outcomes after inguinal LN dissection from rectal or anal canal adenocarcinoma with curative intent, MST was 66.6 months and 5-year OS was 55.2%. These results are noticeably better than previous data reported for inguinal LN metastasis from anal canal or rectal adenocarcinoma (MST, 8–14.8 months; 5-year OS, 0–19.1%) [8, 9, 11, 20]. This discrepancy could be due to the small sample size in the previous studies (8–32 patients) [8, 9, 11, 20], as well as recent developments in chemotherapy and the multidisciplinary team approach.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The present study found that, for long-term outcomes after inguinal LN dissection from rectal or anal canal adenocarcinoma with curative intent, MST was 66.6 months and 5-year OS was 55.2%. These results are noticeably better than previous data reported for inguinal LN metastasis from anal canal or rectal adenocarcinoma (MST, 8–14.8 months; 5-year OS, 0–19.1%) [8, 9, 11, 20]. This discrepancy could be due to the small sample size in the previous studies (8–32 patients) [8, 9, 11, 20], as well as recent developments in chemotherapy and the multidisciplinary team approach.…”
Section: Discussioncontrasting
confidence: 64%
“…These results are noticeably better than previous data reported for inguinal LN metastasis from anal canal or rectal adenocarcinoma (MST, 8–14.8 months; 5-year OS, 0–19.1%) [8, 9, 11, 20]. This discrepancy could be due to the small sample size in the previous studies (8–32 patients) [8, 9, 11, 20], as well as recent developments in chemotherapy and the multidisciplinary team approach. In our study, although almost 80% of patients experienced recurrence after inguinal LN dissection, a multidisciplinary team approach that included surgical treatment and chemotherapy for recurrent tumors could have led to the better prognosis.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Anal adenocarcinoma (AA), which is thought to originate from the columnar epithelium lining the anal glands, is a rare condition, accounting for approximately 1.5%-2.5% of all digestive system cancers[1, 2]. However, the worldwide incidence rate has steadily increased over the years[2]. The anatomical terminology and pathogenesis of this disease are controversial, leading to disparities in both diagnosis and treatment[3].…”
Section: Introductionmentioning
confidence: 99%